Giant mitochondria in cardiomyocytes: cellular architecture in health and disease - Li, Amy; Shami, Gerald J.; Griffiths, Lisa; Lal, Sean; Irving, Helen; Braet, Filip (Basic research in cardiology, 2023)
Giant mitochondria are frequently observed in different disease models within the brain, kidney, and liver. In cardiac muscle, these enlarged organelles are present across diverse physiological and pathophysiological conditions including in ageing and exercise, and clinically in alcohol-induced heart disease and various cardiomyopathies. This mitochondrial aberration is widely considered an early structural hallmark of disease leading to adverse organ function. In this thematic paper, we discuss the current state-of-knowledge on the presence, structure and functional implications of giant mitochondria in heart muscle. Despite its demonstrated reoccurrence in different heart diseases, the literature on this pathophysiological phenomenon remains relatively sparse since its initial observations in the early 60s. We review historical and contemporary investigations from cultured cardiomyocytes to human tissue samples to address the role of giant mitochondria in cardiac health and disease. Finally, we discuss their significance for the future development of novel mitochondria-targeted therapies to improve cardiac metabolism and functionality.